Distribution Channel and the Quality of the Narrow-Barred King Mackerel from Blanakan Fishing Port to Fish Markets - Ernani Lubis; Iin Solihin; Novia Nurul Afiyah (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2019)
Fish is a commodity that has a high nutritional value and highly perishable. The distribution plays an essential role in determining the quality control of the fish to be bought by the consumers. At present, the handling and quality control of the fish, from the fishing port until the fish market, is not proper. The purpose of this study was to determine the distribution channel of mackerel fish (Scomberomorus commerson), the fish handling and to assess the quality of the fish which distibuted from the Blanakan coastal fishing port to the fish market. The results of the kruskal wallis test revealed the influence of the distribution of mackerel fish from Blanakan to the fish market, consist of eight regional fish markets and two local fish markets. Based on the organoleptic assessment, there was a decrease in fish quality by 11% in terms of appearance parameters such as eye, gills, body mucus, odors, and texture .